The effect of using electronic marketing on developing the sports system in the Arab Republic of Egypt - alyasddik Mohamed, Mohamed (International Journal of Psychosocial Rehabilitation, 2024)
The study aims to study the effect of using electronic marketing on developing the sports system in the Arab Republic of Egypt. In light of the theoretical study of the issue of electronic marketing and its impact on the development of the sports system in Egypt, the researcher can determine the general results of the study as follows: The electronic marketing system is unable to achieve its goals in light of the rapid and increasing technological development, which indicates that the traditional marketing system is no longer commensurate with the requirements and developments of the modern era. The electronic marketing system is a flexible marketing system through which it leaves a large area of freedom to market all the elements of sport and through which many advantages can be achieved, including finding a popular market for all sports elements and providing the required money. In light of the results reached, some recommendations can be made as follows: Reducing reliance on the traditional marketing system within sports institutions and replacing them with emarketing programs.